Toward Sustainable E-Waste Management: Bridging Gaps and Insights from General Santos City, Philippines - Garcia, Renante; Marcilla, Allan; Flores, Leonard; Lapong, Edward (Journal of Interdisciplinary Perspectives, 2024)
Electronic waste (e-waste) management in the Philippines remains underexplored, particularly regarding consumer behaviors, with limited research on the disposal practices of residents in General Santos City. This mixed-method study addresses this gap by exploring the psychosocial factors influencing e-waste management in the city using the Knowledge, Attitudes, and Practices (KAP) model across three segments of electronic and electrical equipment (EEE) consumers. Data were collected from 102 participants across five barangays using stratified proportionate sampling via a self-administered survey. Qualitative insights were gathered through an in-depth interview with a key informant from the Solid Waste Management Office. Commercial users show high knowledge (3.68) and positive attitudes (3.81) but lower sustainable disposal practices (3.29). Residential consumers exhibit moderate knowledge (3.36) and attitudes (3.72), with behaviors like hoarding. Educational institutions have the highest knowledge (3.79) and attitudes (3.62) but face adoption challenges. Thus, awareness of environmental and economic impacts alone does not guarantee responsible e-waste disposal. The study emphasizes the need for systemic solutions, such as adopting Extended Producer Responsibility (EPR) at the local level by leveraging the Local Government Code of 1991. Local governments can pass ordinances requiring stakeholders to manage end-of-life EEEs, such as establishing e-waste collection points in commercial business districts. Establishments can adopt EPR practices, partnering with educational institutions and NGOs for take-back programs. Integrating urban mining into local EPR frameworks supports a circular economy, reduces reliance on virgin materials, creates jobs, and mitigates environmental impacts. Optimizing municipal solid waste management to include e- waste processing, alongside the "Best-of-2-Worlds" approach, bridges technological gaps. A robust institutional mechanism and strong political commitment are essential to address the underutilization of the city's Material Recovery Facilities. Embracing "think globally, plan regionally, act locally" helps cities develop sustainable, tailored e-waste strategies.